American College of Surgeons Level I trauma centers outcomes do not correlate with patients' perception of hospital experience. Issue 4 (April 2017) - Joseph, Bellal; Azim, Asad; O'Keeffe, Terence; Ibraheem, Kareem; Kulvatunyou, Narong; Tang, Andrew; Vercruysse, Gary; Friese, Randall; Latifi, Rifat; Rhee, Peter
Abstract : BACKGROUND: The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey is a data collection methodology for measuring a patient's perception of his/her hospital experience, and it has been selected by the Centers of Medicare and Medicaid Services as the validated and transparent national survey tool with publicly available results. Since 2012, hospital reimbursements rates have been linked to HCAHPS data based on patient satisfaction scores. The aim of this study was, therefore, to assess whether HCAHPS scores of Level I trauma centers correlate with actual hospital performance. METHODS: Retrospective analysis of the latest publicly available HCAHPS data (2014–2015) was performed. American College of Surgeons (ACS) verified Level I trauma centers for each state were identified from the ACS registry and then the following data points were collected for each hospital: HCAHPS linear mean scores regarding cleanliness of the hospital, doctor and nurse communication with the patient, staff responsiveness, pain management, overall hospital rating, and patient willingness to recommend the hospital. Our outcome measure were serious complication scores, failure-to-rescue (FTR) scores and readmission-after-discharge scores. Spearman correlation analysis was performed. RESULTS: A total of 119 ACS verified Level I trauma centers across 46 states were included. The median [IQR] overall hospital rating score for Level I trauma centers was 89 (87–90). The mean ± SD score for serious complication was 0.96 ± 0.266, FTR was 123.06 ± 22.5, and readmission after discharge was 15.71 ± 1.07. The Spearman correlation analysis showed that overall HCAHP-based hospital rating scores did not correlate with serious complications (correlation coefficient = 0.14 p = 0.125), FTR (correlation coefficient = −0.15 p = 0.073), or readmission after discharge (correlation coefficient = −0.18 p = 0.053). CONCLUSION: The findings of our study suggest that no correlation exists between HCAHPS patient satisfaction scores and hospital performance for Level I trauma centers. Consequently, the Centers of Medicare and Medicaid Services should reconsider hospital reimbursement decisions based on HCAHP patient satisfaction scores. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III; therapeutic study, level IV.